2006
DOI: 10.1021/la0532196
|View full text |Cite
|
Sign up to set email alerts
|

Cross Metathesis on Olefin-Terminated Monolayers on Si(111) Using the Grubbs' Catalyst

Abstract: This paper reports the functionalization and patterning of olefin-terminated monolayers on Si(111) through cross metathesis. A simple, one-step synthesis of a diolefin--CH2=CH(CH2)9O(CH2)9CH=CH2--was developed from commercially available starting materials. Mixed partially olefin-terminated monolayers of this novel diolefin and 1-octadecene on hydrogen-terminated Si(111) were obtained. The olefins are raised above the rest of the monolayer and thus sterically accessible for further functionalization. Olefin-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…The product was purified by chromatography on silica gel eluting with 30% ethyl acetate/70% hexane. NMR spectra matched those in the literature [19,29]. 1 …”
Section: 4-diphenoxy-2-butene (7c)supporting
confidence: 72%
“…The product was purified by chromatography on silica gel eluting with 30% ethyl acetate/70% hexane. NMR spectra matched those in the literature [19,29]. 1 …”
Section: 4-diphenoxy-2-butene (7c)supporting
confidence: 72%
“…50% conversion. However, the authors suggested possible side reactions between adjacent surface-bound olefins 236 (Fig. 18).…”
Section: O [Edc]b[nhs]mentioning
confidence: 99%
“…Clearly, many researchers recognize the importance of employing multiple analytical techniques to characterize surfaces and materials . However, to better understand the degree to which this message is being put into practice, we selected 13 papers from nine research groups on the topic of surface modification of hydrogen‐terminated, porous, and scribed silicon with carbon–carbon double bond containing reagents . This is an area in which one of us (MRL) has published .…”
Section: Introductionmentioning
confidence: 99%